La documentación conventual custodiada en el fondo antiguo del Archivo Diocesano de Mérida-Badajoz (siglos XVI-XIX) - Pérez Ortiz, María Guadalupe (Documentación de las Ciencias de la Información, 2007)
The present work has like purpose of presenting one important the archivisticas organizations and, simultaneously less well-known of Extremadura, the File Diocesano de Mérida-Badajoz, though conventual documentation. Our research, therefore, two main aims: determining the theoretical foundations on which origin and develop the file, and analyze the conventual documentation conserve in the file.